Cytogenetic study of traffic policemen occupationally exposed to vehicle Exhaust in Erbil City/ Iraqi Kurdistan Region - Sulaiman, Kazhal M. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Police personnel play a pivotal role in any society by ensuring security and stability. They constitute a special occupational group with exposure to violence at their work, which directly and indirectly affects their health. The first aim of this study was to assess the cytogenetic effects of urban air pollution by analyzing the chromosomal aberration frequencies and mitotic index in peripheral blood lymphocytes of traffic policemen in Erbil city. The present study was carried out on 40 traffic policemen who were worked in different streets in Erbil city included four main streets (30, 40 , 60 and 100) Meter streets so many factors were studied included smoking habit and duration of work ( less than five years and more than five years) and 20 controls at different age groups range between (22-50) years. The second objective of the present study is to know the common health problems among traffic policemen in Erbil city. The results suggest that there were a significant increase in the chromosomal aberrations included (Dicentric chromosome, chromatid gap, centromeric break and centromeric gap) in traffic policemen when compared to the controls but significant decreases in mitotic index were shown. The highest value of chromosomal aberrations was centromeric gap and lowest value of mitotic index were both founded in traffic policemen who were worked at 100 Meter street with duration of exposure for more than five years and who were smoker. Also the results suggested different health problems among traffic policemen included (respiratory, skin, eye ,neurologic and infertility problems). Most policemen with health problems are suffering from respiratory, eye and neurologic problems while fewer of them are suffering from infertility problems.